Where Are Pedagogies in Teaching Hospitals? A Call to Action - Hermanto TJ (Asian Journal of Health Research, 2026)
Teaching hospitals and academic medical centers are the heart of medical education, serving as the primary environments where future physicians and allied health professionals are formed [1]. However, a striking imbalance has emerged in institutional discourse. While these centers are founded on a dual mission of service and education, current literature is dominated by management, revenue generation, and financial sustainability [2,3]. Pedagogy the intentional science of learning is conspicuously absent.